PWE-182 The effect of nfΚb pathway deregulation on the progression to oesophageal adenocarcinoma through aberrant BCL3 expression. (22nd June 2015) - Puccio, I; Rodriguez-Justo, M; Butt, MA; Khan, S-U-R; Novelli, M; Lovat, LB; Hamoudi, R
Abstract : Introduction: NFκB pathways have been implicated in many diseases and has been shown to be the link between inflammation and cancer. This pathway is regulated via inhibitor molecules from the IκB family, which BCL3 forms part of. BCL3 functions as an inhibitor to the nuclear translocation of some of the NFκB subunits (p50, p65, RelB, RelA and p52). Not much is known about the role of BCL3 in the regulation of NFκB in upper GI cancer aetiopathogenesis. In this study, we present preliminary data showing that BCL3 has different expression pattern in the Barrett's metaplasia-dysplasia-carcinoma sequence. Method: Paraffin embedded oesophageal specimens were selected from 72 patients, containing normal squamous (n = 14), non-dysplastic Barrett's (n = 15), low grade dysplasia (LGD) (n = 17), high grade dysplasia (HGD) (n = 17) and invasive OA (n = 7). Immunohistochemistry was performed to assess BCL3 expression within the sub-groups. Intensity (0–3+) and extent (0; <1%=1; 1–10%=2; 10–33%=3; 33–66%=4; >66%=5) for staining were scored by 2 expert GI pathologists. The mean for each group was calculated. The relationships between groups were analysed using Mann-Whitney test. Results: 30% (5/17) of patients in the LGD group had no BCL3 expression at all, probably leading to alternative pathways activated as a result of constitutive NFκB activation. Statistically, BCL3 expression was higher in the HGD group compared to the LGD (p = 0.02). Conclusion: This novel study shows variation in BCL3 expression patterns across the groups studied. The LGD group has most cases with BCL3 negative expression. This raises the question as to whether alterations in the NFκB pathway are relevant to the early development of Barrett's neoplasia. Since BCL3 functions as an inhibitor of the nuclear translocation to the NFκB subunits, low expression would lead to the activation of different transcriptomic pathways. Larger sample sizes are needed to improve the statistical power. Further molecular transcriptomic analysis of cases with BCL3 positive and negative expression is warranted. This may shed light on the molecular mechanism of upper GI neoplasia progression and lead to the identification of key therapeutic targets. Disclosure of interest: None Declared.